The Assassination of Anton Cermak, Mayor of Chicago: A Review of His Postinjury Medical Care - Theodore N. Pappas (The Surgery Journal, 2020)
Anton Cermak was the mayor of Chicago in the 1930s. He was injured by an assassin's bullet intended for the president-elect, Franklin Delano Roosevelt. Cermak was taken to a local hospital, treated nonoperatively for his injuries, and initially improved. Cermak's condition deteriorated on the sixth day postinjury, with symptoms that his doctors described as colitis. He died of sepsis on the 19th day after the shooting, and his autopsy revealed a perforated colon causing peritonitis. This study will review Cermak's clinical course and autopsy findings to determine if he died of his gunshot wound or if he died of complications of toxic colitis.